Correction: Transistor application of new picene-type molecules, 2, 9-dialkylated phenanthro[1, 2-b:8, 7-b′]dithiophenes. Issue 12 (28th March 2015) - Kubozono, Yoshihiro; Hyodo, Keita; Mori, Hiroki; Hamao, Shino; Goto, Hidenori; Nishihara, Yasushi
<x xml:space="preserve">Abstract</x> Correction for 'Transistor application of new picene-type molecules, 2, 9-dialkylated phenanthro[1, 2-b:8, 7-b′]dithiophenes' by Yoshihiro Kubozono et al., J. Mater. Chem. C, 2015, 3, DOI: ; Web: 10.1039/c4tc02413c.